Comparison of the number and distribution of chromosomes of three varieties of Nile tilapia (Oreochromis niloticus) - Darmawan Setia Budi; Lailatul Lutfiyah; Arif Habib Fasya; Prayogo Prayogo (Journal of Aquaculture Science, 2019)
The aims of this study is to determine the number and distribution of the chromosomes of three Nile tilapia (Oreochromis niloticus) varieties as basic information in the process of identifying the characteristics of varieties in tilapia. This research was conducted in August-October 2016, at the Unair Banyuwangi PSDKU laboratory. The research procedures included rearing of test fish, immersion of test fish with colchicine solution and tissue preservation, preparation of preparations and staining, and observation. Based on the results of the study, it was found that each variety of tilapia (black, red, and white) showed a difference in the spread of chromosomes, while the number of chromosomes was the same, namely 44 pieces.